FAKTOR-FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL PADA PERUSAHAAN NON KEUANGAN YANG PUBLIK - Yohanes Yohanes (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2014)
The purpose of this research is to examine the influence of assets tangibility, profitability, assets growth, firm size, liquidity, managerial ownership, business risk and non-debt tax shield to capital structure. The population of this research is all non financial companies listed in Indonesia Stock Exchange from 2011 to 2013. Samples are obtained through purposive sampling method, in which only 160 of listed non financial companies in Indonesia Stock Exchange meet the sampling criterias resulting 437 data available are taken as the samples. The research resource are taken from Indonesia Stock Exchange website. This research used multiple regression method to test the effect of each variable in influencing capital structure. The empirical result indicates that tangibility of assets, profitability, assets growth, firm size and liquidity have influence to capital structure. However managerial ownership, business risk and non-debt tax shield have no influence to capital structure.